Speciation of selenium in medicinally important plants and its bioaccessibility - KUNDA N. GAIKWAD; NILIMA S. RAJURKAR (International Journal of Pharma and Bio Sciences, 2016)
In present study highly sensitive and simple spectrophotometric method reported in the literature was modified and employed for speciation of selenium in medicinal plants. Total Selenium and bioaccessible selenium after in-vitro gastric and gastrointestinal method was determined using spectrophotometer and results were also verified with Inductively coupled plasma atomic emission spectroscopy (ICP-AES) technique. The method involves reaction of selenium (IV) with 2, 3 di-aminonapthalene to give the bright colored and strongly fluorescent 4, 5-benzopiazselenol compound. The optimum pH for this reaction was 2 and optimum temperature was 500C. The molar absorptivity of the complex formed was 29.866 × 103 L mol−1cm-1. This method is applicable in the range of 25 - 2000 µg/l of selenium. Highest selenium content was found to be 32 µg/g in Amoora rohitaka (Roxb). An in-vitro study indicates that bioaccessibility of selenium in Sphaeranthus hirtus willed was highest during gastro-intestinal digestion. This result shows that medicinal plants can be a good source of selenium bioaccessibility being high.